Links Between Geological Processes, Microbial Activities & Evolution of Life Microbes and Geology - Dilek, Yildirim; Furnes, Harald; Muehlenbachs, Karlis (Modern Approaches in Solid Earth Sciences, 2008)
Microbial activities influence water-rock interaction processes and chemical transport between the major geochemical reservoirs and the formation/transformation of minerals and rocks, whereas geological processes and geochemical controls influence the microbial ecology in extreme environments. How biological activity influences geological processes and what role these processes played in the geological evolution of the Earth are fundamental questions. How do we recognize the ancient microbial activities in the rock record and what analytical methods do we use to document them to better understand the evolution of life? Can we detect the existence of microbial life in deep time by studying Archaean rocks? Microbial systems in extreme environments and in the deep biosphere may be analogous to potential life on other planetary bodies and hence may be used to investigate the possibilities of extraterrestrial life. This book explores these questions in an interdisciplinary approach, and examines the mode and nature of links between geological processes and microbial activities and their significance for the origin and evolution of life on the Earth and possibly on other planets.